The association between visceral adipocyte hypertrophy and NAFLD in subjects with different degrees of adiposity - Sun, Haixiang; Fang, Da; Wang, Hongdong; Wang, Jin; Yuan, Yue; Huang, Shanshan; Ma, Huayang; Gu, Tianwei; Bi, Yan (Hepatology international, 2023)
Objective To investigate the association between visceral adipocyte hypertrophy and the onset and development of non-alcoholic fatty liver disease (NAFLD) in subjects with different degrees of adiposity. Methods Omental adipose tissue and liver biopsies were collected from obese subjects. NAFLD was defined according to the NASH Clinical Research Network scoring system. Adipocyte size was measured using pathological section analysis. Adipose tissue insulin resistance (Adipo-IR) was calculated as fasting insulin (pmol/L) × fasting free fatty acid concentration (mmol/L). Results In total, 275 obese patients were enrolled, including 158 females and 58 males with NAFLD. In females, adipocyte size was significantly larger in NAFLD participants as compared to the controls (99.37 ± 14.18 vs . 84.14 ± 12.65 μ m, p < 0.001). Moreover, adipocyte size was larger in females with non-alcoholic steatohepatitis (NASH) as compared to those with non-alcoholic fatty liver (NAFL) (101.45 ± 12.77 vs . 95.79 ± 15.80 μ m, p = 0.015). Mediation analysis showed that adipocyte size impacted the NAFLD activity score through Adipo-IR ( b = 0.007 [95% bootstrap CI 0.002, 0.013]). Furthermore, the females were divided into: Q1 (BMI < 32.5 kg/m 2 ), Q2 (BMI 32.5–35.5 kg/m 2 ), Q3 (BMI 35.5–38.8 kg/m 2 ) and Q4 (BMI ≥ 38.8 kg/m 2 ) according to BMI quartiles. Omental adipocyte size was larger in NAFLD subjects in Q1–Q3, but not in Q4. No similar results were observed in males. Conclusion For the first time, we reported that visceral adipocyte hypertrophy was associated with the onset and progression of NAFLD in mild to moderate adiposity but not in severe obesity, which may be mediated by adipose tissue insulin resistance.